1994
DOI: 10.1093/infdis/170.supplement_1.s24
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis Of Measles Virus Infection: An Hypothesis For Altered Immune Responses

Abstract: Measles virus causes a severe systemic illness. The rash occurs simultaneously with the onset of the effector phase of the antiviral immune response and substantial evidence of immune activation. This immune response is effective in clearing virus and in establishing long-term resistance to reinfection but is associated with immune suppression, autoimmune encephalomyelitis, and increased susceptibility to secondary infections. This apparent paradox may be explained in part by preferential long-term activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
3

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(82 citation statements)
references
References 85 publications
3
76
0
3
Order By: Relevance
“…suppression include lymphopenia and proliferative unresponsiveness of peripheral blood lymphocytes to mitogens (Griffin et al, 1994;Schneider-Schaulies & ter Meulen, 2002). The ability of myeloid dendritic cells (DCs) to both initiate T cell activation and mediate viral transport to secondary lymphatics has determined that they are central to MV-specific immunity and immunosuppression (Pollara et al, 2005;Steinman et al, 2003).…”
Section: Hallmarks Of Measles Virus (Mv)-induced Immuno-mentioning
confidence: 99%
“…suppression include lymphopenia and proliferative unresponsiveness of peripheral blood lymphocytes to mitogens (Griffin et al, 1994;Schneider-Schaulies & ter Meulen, 2002). The ability of myeloid dendritic cells (DCs) to both initiate T cell activation and mediate viral transport to secondary lymphatics has determined that they are central to MV-specific immunity and immunosuppression (Pollara et al, 2005;Steinman et al, 2003).…”
Section: Hallmarks Of Measles Virus (Mv)-induced Immuno-mentioning
confidence: 99%
“…Both disruption of mucosal surfaces and the immunosuppression associated with measles virus predispose to secondary infection, which is thought to occur in over half of children with measles associated pneumonia (2,24,25). We found that the disease severity was associated with the higher peripheral leukocyte, neuthrophil counts and higher serum CRP levels.…”
Section: Discussionmentioning
confidence: 64%
“…A direct viral action is suggested by the results of autopsy reports [15,16], in which viral antigen was found in a variety of epithelial cell types, including biliary duct epithelium. Moreover, we speculate that the particular tropism of measles virus for vascular endothelial cells [3,17] could play a role in the genesis of microangiopathy observed in AAC [10]. The role of bile stasis induced by fever, dehydration and prolonged fasting may also be evocated.…”
Section: Discussionmentioning
confidence: 99%